The Role of Bone Grafts in Preventing Medication-Related Osteonecrosis of the Jaw: Histomorphometric, Immunohistochemical, and Clinical Evaluation in Animal Model - Silva, Jonathan Ribeiro da; Balbas, Maria Cristina de Moraes; Correa, Caroline Agueda; Zanela, Manuella; Okamoto, Roberta [UNESP]; Pereira, Rodrigo dos Santos; Homsi, Nicolas; Hochuli-Vieira, Eduardo [UNESP] (Sage Publications Inc, 2021)
Objective: To evaluate the effects of inorganic bovine bone graft (Lumina Bone, Criteria, Brazil) and beta-tricalcium phosphate (beta-TCP) graft (ChronOS, Synthes, Brazil) in rats with the risk of developing post-extraction medication-related osteonecrosis of the jaw (MRONJ). Methods: Eighteen male Wistar rats weighing 350 to 450 g were induced to develop MRONJ using zoledronic acid for 5 weeks. In the sixth week, the right maxillary first molar was extracted. The animals in Group I (G1) did not receive bone grafts after tooth extraction, while Group II (G2) animals received inorganic bovine bone grafts, and Group III (G3) animals received beta-tricalcium phosphate (beta-TCP) grafts. Clinical evaluation and histomorphometric and immunohistochemical analyses were performed. ANOVA and Tukey's statistical tests were used and a level of significance was considered to be 5%. Results: In the clinical evaluation, animals from G2 and G3 did not present clinical manifestations of osteonecrosis, unlike the control group (G1) animals, which presented necrotic bone tissue exposure in all samples. In the histomorphometric evaluation, animals in G3 showed greater formation of bone tissue (66%) and less formation of bone lacuna (18%) than animals in G1 (58%/32%) and in G2 (59%/27%) (P < 0.05). Moderate (++) immunostaining was observed in G2 and G3 for RANKL, TRAP, and OC, while G1 showed moderate (++) labeling for OC and mild (+) immunostaining for TRAP and RANKL. Conclusions: Greater formation of bone tissue and fewer bone lacunae were found in animals treated with beta-TCP. In clinical evaluation, bone graft groups presented with the clinical manifestation of MRONJ and showed higher intensity of immunostaining for TRAP and RANKL. Despite the limitations of experimental animal studies, the results of this work may assist in the development of future clinical research for the prevention of MRONJ.
Keywords: bisphosphonate; osteonecrosis; bone graft; bisphosphonate-associated osteonecrosis of the jaw; rats; Wistar